A cucumber biomass powder enhanced p(aa-co-am) superabsorbent hydrogel, a preparation method and application thereof

CN122878698APending Publication Date: 2026-10-09SOUTH CHINA NORMAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611242945.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,无机填料在聚合体系中常存在分散不均、界面结合不足等问题,导致吸液后结构稳定性下降,在盐环境中性能衰减尤为明显,因而对吸液倍率、吸液速率与离心保留能力的改善幅度有限

Benefits of technology

本发明以黄瓜生物质粉末CBP作为生物基增强相和亲水导水骨架,将其引入P(AA-co-AM)共聚交联网络中,实现材料绿色化与低成本原料替代,获得P(AA-co-AM)/CBP SAP复合高吸水性水凝胶。与现有传统单一聚丙烯酸盐类SAP相比,本发明不仅依靠AA链段中的-COO-提供静电排斥和渗透压吸液驱动力,还通过AM链段中的-CONH2以及黄瓜生物质粉末CBP中的-OH、部分含氧官能团等非离子亲水位点增强水分子结合能力,从而缓解纯羧酸盐体系在含盐环境中因电荷屏蔽导致吸液能力下降的问题。与此同时CBP在水相反应体系中经预分散后参与复合网络构筑。这是因为CBP中的多糖类骨架及其表面羟基可与P(AA-co-AM)链段形成氢键、物理缠结或界面相互作用,增强聚合物网络的稳定性;而且CBP的颗粒含有的多糖、纤维素相关骨架及羟基等亲水基团,可为水凝胶网络提供额外亲水位点,增强材料与水分子的结合能力,作为生物质骨架或支撑相嵌入P(AA-co-AM)网络中,有助于复合水凝胶形成更加疏松、连通的多孔结构,有利于液体快速渗入和扩散,降低液体进入凝胶内部的扩散阻力,缩短吸液路径,从而提高吸液速率和吸液倍率。另外CBP骨架还能与MBA形成的化学交联网络共同构成支撑结构,可在一定程度上抑制凝胶在吸液后的过度松散和塌陷,提高材料在离心或外力作用下的保液能力(离心保留能力)。因此,本发明能够在吸液倍率、吸液速率和离心保留之间实现较好的协同平衡。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878698A_ABST
    Figure CN122878698A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer synthesis, and relates to a cucumber biomass powder reinforced P(AA-co-AM) superabsorbent hydrogel as well as a preparation method and application thereof. The application realizes material greenization and low-cost raw material replacement by introducing cucumber biomass powder as a renewable biomass skeleton / reinforcing phase into a P(AA-co-AM) crosslinked network, that is, by reasonably matching raw materials, appropriately controlling temperature, time and post-treatment conditions, crosslinking the copolymer network and the cucumber biomass powder skeleton through redox initiation and a crosslinking agent in an aqueous phase system, and cooperatively constructing a stable biomass skeleton-acrylic acid / acrylamide copolymerization-crosslinking three-dimensional composite network gel structure, so that the prepared P(AA-co-AM) / CBP SAP has higher salt resistance and enhanced actual use adaptability. Meanwhile, water absorption rate, liquid absorption rate and centrifugal retention are cooperatively optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer synthesis technology, and specifically relates to a P(AA-co-AM) superabsorbent hydrogel reinforced with cucumber biomass powder, its preparation method and application. Background Technology

[0002] Superabsorbent polymers (SAPs) are key materials for the absorbent core of hygiene products, with core performance characteristics including absorbance, absorption rate, and retention capacity in saline body fluids. Existing polyacrylate-based SAPs exhibit a decrease in absorbance due to the electrostatic repulsion of carboxylate groups by cations in electrolyte solutions, which reduces the osmotic pressure difference. Furthermore, there is an inherent contradiction between absorbance, absorption rate, and centrifugal retention capacity, making simultaneous optimization difficult: excessively low crosslinking density results in insufficient gel strength and poor retention capacity; excessively high crosslinking density reduces network pore size and restricts chain segment movement, further decreasing absorbance and absorption rate. Therefore, achieving a balance between absorbance, absorption rate, and centrifugal retention capacity in saline environments is a critical technical challenge for SAP materials.

[0003] Currently available commercial SAP materials based on petroleum-based acrylate systems primarily rely on the -COO group in the acrylic acid chain for their high liquid absorption capacity. - The electrostatic repulsion and osmotic pressure driving force provided by the functional groups. To improve water absorption rate and centrifugal retention capacity, some studies have modified inorganic fillers by introducing surface-rich hydrophilic groups such as hydroxyl groups. The hydrophilic groups of the modified inorganic fillers can increase additional water binding sites, and the rigid skeleton can prevent the tight packing of chain segments, promote the formation of micropores and capillary channels, and accelerate water permeation. At the same time, the fillers can act as physical cross-linking points, enhancing the gel network strength through interfacial interactions such as hydrogen bonds, and improving the liquid retention capacity under pressure or centrifugal conditions. However, inorganic fillers often suffer from uneven dispersion and insufficient interfacial bonding in polymerization systems, leading to decreased structural stability after liquid absorption, with performance degradation being particularly significant in salt environments. Therefore, the improvement in liquid absorption ratio, liquid absorption rate, and centrifugal retention capacity is limited. In addition, such modifications still mainly rely on petroleum-based raw materials, failing to fundamentally solve the dependence on non-renewable resources. Summary of the Invention

[0004] To address the shortcomings of the existing technology, the present invention aims to provide a cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel, its preparation method, and its application. The P(AA-co-AM) / CBPSAP prepared by this method is environmentally friendly and can maintain a high liquid absorption ratio and volume stability even under electrolyte solution (such as 0.9% physiological saline), achieving synergistic optimization between high water absorption ratio, high liquid absorption rate, and centrifugal retention.

[0005] The present invention provides a P(AA-co-AM) superabsorbent hydrogel reinforced with cucumber biomass powder, which is prepared by using water as solvent, acrylic acid and acrylamide as reactive monomers, cucumber biomass powder as inorganic filler, adding initiator and crosslinking agent, undergoing polymerization and crosslinking reaction, and then drying, pulverizing and sieving.

[0006] By introducing renewable cucumber biomass powder, the hydrophilicity, porous structure, and network stability of the material are improved through acrylic acid / acrylamide copolymer crosslinking network design, thereby enhancing its liquid absorption capacity, absorption rate, and centrifugal retention performance in saline liquids. Specifically, through pre-dispersion of cucumber biomass powder, partial neutralization of acrylic acid, acrylic acid / acrylamide copolymerization, MBA crosslinking, and redox initiation by APS and NaHSO3, CBP is incorporated into the P(AA-co-AM) crosslinking network as a biomass reinforcing phase and a hydrophilic and water-conducting framework, ultimately obtaining a P(AA-co-AM) / CBP composite superabsorbent hydrogel.

[0007] CBP contains polysaccharides, cellulose-related backbones, and hydrophilic groups such as hydroxyl groups, which can provide additional hydrophilic sites for the hydrogel network and enhance the material's binding ability with water molecules. CBP can be embedded in the P(AA-co-AM) network as a biomass backbone or support phase, enabling the composite hydrogel to form a more loose and interconnected porous structure, which facilitates rapid liquid penetration and diffusion, thereby improving the liquid absorption rate and absorption capacity. The -OH functional groups on the CBP surface can interact with the -COOH and -COO groups in the P(AA-co-AM) segments. - Groups such as -CONH2 form hydrogen bonds, physical entanglements, or interfacial interactions, enhancing network structure stability and improving liquid retention and thermal stability. The nonionic hydrophilic sites provided by CBP and AM are less affected by the charge shielding of salt ions than by the simple -COO group. - In terms of structure, the biomass framework of CBP can serve as a support phase and a water-conducting framework, promoting the formation of a loose, interconnected porous structure and reducing liquid diffusion resistance. These structural changes improve the material's liquid uptake ratio, uptake rate, salt solution adaptability, and centrifugal retention capacity. Therefore, it helps the material maintain good liquid uptake capacity in saline environments such as 0.9% NaCl and artificial urine.

[0008] Preferably, the mass of acrylic acid is 27.5% of the mass of water, and the mass ratio of acrylic acid to acrylamide is 2:1.

[0009] Acrylic acid (AA) is the main component providing -COOH / -COO in the system. -The content of monomers with hydrophilic ionic groups directly affects the effective monomer concentration and the final network cross-linking structure in the polymerization system. When the acrylic acid concentration is too low, there are insufficient hydrophilic segments to form in the polymerization system, resulting in an incomplete network structure and a decrease in liquid uptake. Conversely, when the acrylic acid content is too high, the system viscosity increases rapidly, easily leading to excessively rapid local polymerization and uneven network cross-linking, forming locally dense structures that limit gel expansion. Therefore, an AA content of 27.5% is beneficial for forming a more uniform and stable three-dimensional cross-linked network. When AA and AM are copolymerized at a mass ratio of 2:1, the network contains both ionic -COO groups provided by AA and... - The group also contains a nonionic -CONH2 hydrophilic group provided by AM. Among them, -COO - It provides strong electrostatic repulsion and osmotic pressure driving force, increasing the liquid absorption rate; while -CONH2 is less affected by salt ion shielding and can maintain good hydrophilicity and liquid absorption stability in saline environments such as 0.9% NaCl and artificial urine. Therefore, this ratio achieves a good balance between high liquid absorption rate and salt resistance.

[0010] Under this AA / AM ratio condition, the P(AA-co-AM) segment contains both -COOH and -COO. - Functional groups such as -CONH2 can form hydrogen bonds and interfacial interactions with -OH groups in cucumber biomass powder (CBP), thereby enhancing the bonding between CBP and the polymer network and promoting the formation of a more stable and interconnected porous structure. Appropriate AA concentration and AA / AM ratio can prevent the network from being too loose or too dense. On the one hand, it can maintain a large network free volume and liquid diffusion channels, improving the liquid absorption rate and absorption ratio; on the other hand, it can maintain sufficient network strength, reducing gel collapse after liquid absorption and improving centrifugal retention capacity. Therefore, this parameter can improve problems such as uneven biomass dispersion, insufficient bonding with the polymer network, poor structural stability after liquid absorption, and performance degradation under salt conditions.

[0011] Preferably, the amount of cucumber biomass powder added is 6% to 14% of the mass of acrylic acid, and the concentration of the CBP dispersion system obtained by dispersing cucumber biomass powder in solvent is 92.3 mg / mL to 215.4 mg / mL.

[0012] Within this suitable addition range, the hydroxyl and other functional groups in the CBP component can provide sufficient reaction and binding sites for the copolymer network, promoting the formation of a more uniform three-dimensional network structure. If the addition amount is too high (i.e., the concentration is too large), the viscosity of the system will increase significantly, resulting in limited mass transfer and free radical diffusion, making the polymerization and crosslinking processes prone to local heterogeneity. At the same time, too many reaction sites will make free radicals more inclined to form multi-point connections on the surface of CBP particles, causing an abnormally high local crosslinking density in the network, thereby limiting the swelling capacity of the gel. At this addition amount, CBP helps the hydrogel form a more loose and interconnected porous structure, shortening the diffusion path of water molecules, thereby significantly improving the liquid absorption rate and ratio; on the other hand, the rigid cellulose skeleton in the CBP component can effectively inhibit gel disintegration caused by excessive swelling, while the hydrogen bond entanglement formed between CBP and P(AA-co-AM) segments can limit excessive relaxation of the segments, enhance swelling stability and structural integrity, and thus improve the liquid retention capacity under pressure or centrifugation. If the addition amount exceeds 14%, excess CBP will occupy a large volume fraction in the form of solid particles, reducing the effective swelling space and limiting the extension of polymer network segments. Pure acrylate networks are easily weakened by ion shielding effects in salt solutions, leading to a sharp drop in liquid absorption performance. However, the abundant nitrogen-free extract and coarse fiber fraction in CBP provide a large number of nonionic -OH sites, and its protein components also provide -NH / -CONH sites. - Isopolar sites. With a reasonable introduction amount of 6% to 14%, the hydrophilic groups can form stronger hydration and hydrogen bonding within the gel, effectively compensating for the osmotic pressure loss caused by charge shielding, enabling the material to maintain high absorption and liquid retention levels even in saline environments such as 0.9% NaCl and artificial urine.

[0013] Preferably, the initiator is ammonium persulfate and NaHSO3, the total mass of the initiator is 0.6% to 1.4% of the mass of acrylic acid, the mass ratio of ammonium persulfate to NaHSO3 is fixed at 2.2:1 (the ratio of the total mass of the two and the mass of acrylic acid varies, but the mass ratio between APS and sodium bisulfite is fixed, i.e.: mAPS:mNaHSO3=2.2:1), the concentration of the solution formed by ammonium persulfate dissolved in the solvent is 59.3 mg / mL to 138.6 mg / mL, and the concentration of the solution formed by sodium bisulfite dissolved in the solvent is 27.0 mg / mL to 63.0 mg / mL.

[0014] The redox initiation system composed of APS and NaHSO3 can efficiently generate reactive species such as sulfate radicals under heating conditions. These reactive radicals can extract hydrogen from the -OH groups on the surface of cucumber biomass powder (CBP), forming macromolecular radicals on the biomass framework, thereby providing grafting active sites.

[0015] The total initiator content was limited to 0.6%–1.4% of the acrylic acid mass, and the mass ratio of ammonium persulfate to NaHSO3 was fixed at 2.2:1 to ensure a moderate and stable free radical generation rate. If the initiator content was too high (above 1.4%), the system would generate excessive free radicals in the early stages of the reaction, making it easier for local cross-linking and densification to form at the interface of CBP multiphase particles, thereby disrupting the uniformity of the gel's internal structure and leading to uneven microscopic dispersion. This limited range avoided explosive polymerization and excessive local cross-linking. The initiator dosage directly determines the average kinetic chain length and pore size of the polymer. If the initiator content was below 0.6%, the number of free radical active centers in the system was insufficient, leading to incomplete polymerization and the formation of an incomplete network with a large amount of soluble components or sparse cross-linking points. After liquid absorption, the network was prone to structural loosening (i.e., poor structural stability). Controlling the dosage within an appropriate range promoted polymer chain growth and the improvement of the cross-linking network, constructing a gel with an effective three-dimensional spatial structure, thereby enhancing its swelling capacity. If excessive amounts are used, the probability of chain termination increases significantly, leading to a shortened average kinetic chain length, a decrease in polymer molecular weight, and a smaller mesh size. This severely restricts network expansion and reduces liquid absorption performance. This concentration limit ensures that the network has suitable strength and pore size, perfectly balancing the liquid absorption ratio, absorption rate, and liquid retention capacity against centrifugal force.

[0016] By precisely controlling the initiation system, not only is the network fully formed, but the salt-resistant polysaccharide component in the CBP is also stably integrated into the three-dimensional cross-linked network. This allows the material to continuously resist the ion shielding effect in an electrolyte environment by relying on the dense hydrogen bonds and hydrophilic channels provided by the CBP framework. From the perspective of structural integrity, this prevents the loss or phase separation of the salt-resistant active component and ensures high water absorption performance in salt solutions.

[0017] Preferably, the crosslinking agent is N,N'-methylenebisacrylamide, the mass of the crosslinking agent is 0.02wt%~0.06wt% of the mass of acrylic acid, and the concentration of the solution formed by dissolving the crosslinking agent in the solvent is 2.88mg / mL~8.64mg / mL.

[0018] Crosslinking density is the main factor controlling the swelling capacity of superabsorbent polymers (SAPs). Crosslinking agents react with the growing chains to link different PAA-AM segments. Within this range, the crosslinking agent's mass is 0.02wt%~0.06wt% of the acrylic acid mass; this concentration allows for the construction of a complete three-dimensional network with suitable pore size. If the MBA concentration is higher than 0.06wt%, the excessive crosslinking density leads to a smaller average pore diameter and shorter molecular chain segments between crosslinking points. This increases the elastic recoil force of the SAP during water absorption and swelling, limiting network expansion and hindering water molecule entry, thus resulting in poor liquid absorption performance. If the MBA concentration is lower than 0.02wt%, the crosslinking density is too low, preventing the polymer chains from effectively forming a complete three-dimensional network through chemical bonds. This causes some of the gel to transform into a water-soluble resin after water absorption, reducing polymer density and making it unable to maintain its post-absorption structure (i.e., poor structural stability), resulting in extremely poor liquid retention under centrifugation or pressure. The appropriate degree of chemical crosslinking, combined with the rigid constraint of the CBP framework, ensures that the SAP crosslinked network does not expand indefinitely, while also providing sufficient elastic recoil force after liquid absorption. In saline body fluid environments, even if the electrostatic repulsion of polymer segments weakens due to the ion shielding effect, this stable three-dimensional crosslinked network still prevents the structure from collapsing completely, thereby maintaining pore connectivity and ensuring the material's liquid absorption capacity and stability in salt solutions.

[0019] Preferably, sodium hydroxide is also added to the reaction system to adjust the degree of neutralization of acrylic acid to 65%~85%, and the mass of NaOH is 36.1%~47.2% of the mass of acrylic acid.

[0020] The addition of an acrylic acid solution with a neutralization degree of 65%–85% is to simultaneously introduce acrylic acid and sodium acrylate structural units into the system, so that the polymerized network contains both -COOH and -COO. - / Na + Hydrophilic ionic groups are introduced. Acrylamide solution is added because acrylamide can copolymerize with acrylic acid, introducing nonionic hydrophilic groups such as -CONH2. On one hand, -CONH2 can enhance the material's ability to bind water molecules through hydrogen bonding; on the other hand, unlike -COO... - Because it relies so strongly on charge repulsion, it is less affected by ion shielding in salt solutions, which is beneficial for improving the material's absorption stability in 0.9% NaCl, physiological saline, or artificial urine.

[0021] Preferably, the reaction temperature of the reaction system is 65℃~85℃.

[0022] The pre-dispersion and subsequent cross-linking copolymerization reactions of cucumber biomass powder (CBP) were both controlled within the range of 65℃ to 85℃. This temperature range was determined after comprehensive consideration and is considered as an optimal reaction temperature range. Below 65℃, the dispersion and polymerization initiation efficiency of CBP are insufficient, making polymerization difficult to occur; above 85℃, the polymerization reaction is too rapid, easily leading to local cross-linking and densification of the network, thus affecting the liquid absorption performance of the material. Therefore, the reaction is preferably carried out at 65℃ to 85℃, with 70℃ being the optimal reaction temperature. The overall reaction system is controlled within the range of 65℃ to 85℃, and it is not required that AM, NaOH, cross-linking agent, or initiator solution be preheated to this temperature separately before addition.

[0023] This invention provides a method for preparing a cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel, comprising the following steps: Preparation of cucumber biomass powder; Cucumber biomass powder was mixed with deionized water, heated and stirred to disperse, and a uniform cucumber biomass dispersion system was obtained. While maintaining the temperature, acrylamide solution and acrylic acid solution with adjusted neutralization degree were stirred and added to the cucumber biomass dispersion system. Then, a crosslinking agent and an initiator were added in sequence to carry out a crosslinking copolymerization reaction. After the reaction was completed, the product was cooled and taken out, immersed in anhydrous ethanol and filtered, dried to constant weight, pulverized and sieved to obtain P(AA-co-AM) superabsorbent water resin.

[0024] Preferably, the P(AA-co-AM) superabsorbent hydrogel reinforced with cucumber biomass powder has an absorption rate of 142.72 g / g for 0.9% NaCl, an absorption rate of 2801.00 g / g for deionized water, and the central vortex disappears after 48 s when 0.9% NaCl is absorbed. The centrifugal retention is as high as 73.17 g / g, and the centrifugal retention rate is 51.27%.

[0025] This invention also provides the application of a cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel in hygiene and care products.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention uses cucumber biomass powder (CBP) as a bio-based reinforcing phase and a hydrophilic, water-conducting framework, introducing it into a P(AA-co-AM) copolymer crosslinking network to achieve green material production and low-cost raw material substitution, obtaining a P(AA-co-AM) / CBP SAP composite superabsorbent hydrogel. Compared with existing traditional single polyacrylate SAPs, this invention relies not only on the -COO in the AA segments... -It provides electrostatic repulsion and osmotic pressure driving force for liquid absorption, and also enhances the water molecule binding ability through nonionic hydrophilic sites such as -CONH2 in the AM chain segment and -OH and some oxygen-containing functional groups in cucumber biomass powder CBP, thereby alleviating the problem of decreased liquid absorption capacity of pure carboxylate system in salt environment due to charge shielding. At the same time, CBP participates in the construction of composite network after pre-dispersion in aqueous reaction system. This is because the polysaccharide backbone and its surface hydroxyl groups in CBP can form hydrogen bonds, physical entanglements or interfacial interactions with P(AA-co-AM) chain segments, enhancing the stability of polymer network; moreover, the polysaccharide, cellulose-related backbone and hydroxyl groups contained in CBP particles can provide additional hydrophilic sites for hydrogel network, enhance the material's binding ability with water molecules, and embed as biomass backbone or support phase in P(AA-co-AM) network, which helps to form a more loose and interconnected porous structure of composite hydrogel, which is conducive to rapid liquid penetration and diffusion, reduces the diffusion resistance of liquid entering the gel interior, shortens the liquid absorption path, and thus improves the liquid absorption rate and liquid absorption ratio. Furthermore, the CBP framework, together with the chemical cross-linking network formed by MBA, can constitute a supporting structure, which can, to a certain extent, inhibit excessive loosening and collapse of the gel after liquid absorption, and improve the liquid retention capacity of the material under centrifugation or external force (centrifugal retention capacity). Therefore, this invention can achieve a good synergistic balance between liquid absorption ratio, liquid absorption rate, and centrifugal retention.

[0027] Experimental results show that the P(AA-co-AM) / CBP SAP prepared in this invention achieved absorption rates of 2801.00 g / g, 142.72 g / g, and 64.83 g / g for deionized water, 0.9 wt% NaCl solution, and artificial urine, respectively, at a specified absorption time of 30 min. The centrifugation retention reached 73.17 g / g, which is significantly better than the P(AA-co-AM) SAP control sample without CBP. This indicates that the introduction of CBP can effectively improve the material's liquid absorption performance, salt environment adaptability, and liquid retention performance.

[0028] Furthermore, the cucumber biomass powder used in this invention does not require complex chemical modification. It can be used for hydrogel preparation simply by drying and pulverizing. The process is simple, the raw materials are widely available, which helps to reduce dependence on petroleum-based raw materials, improve the greenness and sustainability of materials, and is suitable for fields such as absorbent core materials for hygiene products. Attached Figure Description

[0029] Figure 1 This is a flowchart of the preparation process of cucumber biomass powder CPB.

[0030] Figure 2 This is a flowchart of the preparation process of P(AA-co-AM) / CBP SAP according to the present invention.

[0031] Figure 3This is a schematic diagram of the formation and swelling mechanism of the P(AA-co-AM) / CBP SAP composite network.

[0032] Figure 4 FTIR spectra of CBP, P(AA-co-AM) SAP prepared in Comparative Example 1, P(AA-co-AM) / CBPSAP prepared in Example 1, and mechanical mixtures of P(AA-co-AM) SAP and CBP prepared in Comparative Example 2; wherein (a) is CBP; (b) is P(AA-co-AM) SAP; (c) is P(AA-co-AM) / CBP SAP; and (d) is a mechanical mixture of P(AA-co-AM) SAP and CBP.

[0033] Figure 5 The images are scanning electron microscope (SEM) images of freeze-dried P(AA-co-AM) SAP and P(AA-co-AM) / CBP SAP, where (a) is a SEM image of pure P(AA-co-AM) SAP magnified 50 times; (b) is a SEM image of pure P(AA-co-AM) SAP magnified 200 times; (c) is a SEM image of pure P(AA-co-AM) SAP magnified 1000 times; (d) is a SEM image of P(AA-co-AM) / CBP SAP magnified 50 times; (e) is a SEM image of P(AA-co-AM) / CBP SAP magnified 200 times; and (f) is a SEM image of P(AA-co-AM) / CBP SAP magnified 1000 times.

[0034] Figure 6 The liquid absorption performance curves of P(AA-co-AM) / CBP SAP are shown below; where (a) represents the change in total initiator content; (b) represents the change in crosslinking agent content; (c) represents the change in CBP content; (d) represents the change in AA neutralization degree; and (e) represents the change in reaction temperature.

[0035] Figure 7 The image shows the shearing state of the P(AA-co-AM) / CBP SAP sample.

[0036] Figure 8 for Figure 7 A diagram showing the state of the dried and pulverized sample.

[0037] Figure 9 for Figure 8 A diagram showing the state of a small sample after deionization has been removed from a petri dish.

[0038] Figure 10 for Figure 8 A diagram showing the state of a small sample after absorbing physiological saline.

[0039] Figure 11 for Figure 8 A diagram showing the state of a small sample after absorbing artificial urine.

[0040] Figure 12 XRD plots for P(AA-co-AM) SAP, P(AA-co-AM) / CBP SAP, and CBP.

[0041] Figure 13 TGA diagrams for P(AA-co-AM) SAP, P(AA-co-AM) / CBP SAP, and CBP. Detailed Implementation

[0042] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.

[0043] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in Examples 1 to 18, preferred embodiments are described in this invention to avoid redundancy. However, this invention is not limited to these, but can be specifically implemented in other ways within the scope of the technical solutions defined in the appended claims. All raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.

[0044] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0045] The following Examples 1 and Comparative Example 1 are developed according to the self-made SAP formula table, as detailed in Table 1. Table 1 shows the recipes for homemade SAP products. Example 1 A method for preparing a cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel includes the following steps: (1) Preparation of cucumber biomass powder CBP Fresh cucumbers were selected, peeled, and cored. The cucumber flesh was then sliced ​​into uniform thin slices. The slices were air-dried naturally under clean and ventilated conditions for 3 days to allow for preliminary dehydration. The pre-dried sample was then transferred to a vacuum drying oven and vacuum-dried at 75°C for 8 hours to remove residual moisture. After drying, the sample was removed, cooled to room temperature, and then pulverized to obtain cucumber biomass powder (CBP). This powder was then sealed and stored for later use. Figure 1 As shown.

[0046] (2) The preparation steps of P(AA-co-AM) / CBP SAP products are as follows: Figure 2 As shown: S1. Weigh the raw materials according to the following ingredients and proportions.

[0047] The amount of H2O added is 5.2364g, of which the mass of acrylic acid is 27.5% of the mass of water, and the mass ratio of acrylic acid to acrylamide is 2:1; The amount of cucumber biomass powder added was 10% of the mass of acrylic acid; The mass ratio of ammonium sulfate to NaHSO3 was fixed at 2.2:1; the total mass of ammonium sulfate and NaHSO3 was 0.8% of the mass of acrylic acid. The mass of N,N'-methylenebisacrylamide is 0.04% of the mass of acrylic acid.

[0048] Sodium hydroxide was used to adjust the degree of neutralization of acrylic acid to 75%. The mass of NaOH was 41.6% of the mass of acrylic acid.

[0049] S2. Cucumber biomass powder (CBP) and deionized water were added to a 50 mL glass reaction tube and pre-dispersed magnetically in a 70 °C water bath for 30 min to obtain a homogeneous CBP dispersion system. Then, acrylic acid (AA) with a neutralization degree of 75% and acrylamide (AM) solution were added. Under continuous stirring, N,N′-methylenebisacrylamide (MBA), ammonium persulfate (APS) solution, and ammonium sulfate and sodium bisulfite (NaHSO3) solution were added sequentially. The reaction was then continued for 30 min under controlled temperature to complete the crosslinking copolymerization reaction.

[0050] S3. After the reaction is complete, the product is cooled and removed, then immersed in anhydrous ethanol and filtered to remove unreacted monomers and soluble components. The sample is then dried at 75°C to constant weight, pulverized, and passed through a 40-mesh sieve to obtain P(AA-co-AM) superabsorbent hydrogel, denoted as P(AA-co-AM) / CBP SAP product. The shearing state diagram of the P(AA-co-AM) / CBP SAP sample is shown below. Figure 7 As shown, the state diagram of the dried and pulverized sample is as follows. Figure 8 As shown.

[0051] Example 2 The difference between Example 2 and Example 1 is that the amount of cucumber biomass powder added in claim 1 is replaced by 8% instead of 10%, while the rest is the same as in Example 1.

[0052] Example 3 The difference between Example 3 and Example 1 is that the amount of cucumber biomass powder added in claim 1 is replaced by 6% instead of 10%, while the rest is the same as in Example 1.

[0053] Example 4 The difference between Example 4 and Example 1 is that the amount of cucumber biomass powder added in claim 1 is replaced with 12% instead of 6%, while the rest is the same as in Example 1.

[0054] Example 5 The difference between Example 5 and Example 1 is that the amount of cucumber biomass powder added in claim 1 is replaced by 14% instead of 6%, while the rest is the same as in Example 1.

[0055] Example 6 The difference between Example 6 and Example 1 is that the AA neutralization degree change of 75% in claim 1 is replaced with 65%, and the mass of NaOH is 36.1% of the mass of acrylic acid. Everything else is the same as in Example 1.

[0056] Example 7 The difference between Example 7 and Example 1 is that the AA neutralization degree change of 75% in claim 1 is replaced with 70%, and the mass of NaOH is 38.9% of the mass of acrylic acid. Everything else is the same as in Example 1.

[0057] Example 8 The difference between Example 8 and Example 1 is that the AA neutralization change of 75% in claim 1 is replaced with 80%, while the rest is the same as in Example 1.

[0058] Example 9 The difference between Example 9 and Example 1 is that the AA neutralization change of 75% in claim 1 is replaced with 85%, while the rest is the same as in Example 1.

[0059] Example 10 The difference between Example 10 and Example 1 is that the mass ratio of ammonium sulfate to NaHSO3 is fixed at 2.2:1; the total mass of ammonium sulfate and NaHSO3 is 0.6% of the mass of acrylic acid, and everything else is the same as in Example 1.

[0060] Example 11 The difference between Example 11 and Example 1 is that the mass ratio of ammonium sulfate to NaHSO3 is fixed at 2.2:1; the total mass of ammonium sulfate and NaHSO3 is 0.7% of the mass of acrylic acid, and everything else is the same as in Example 1.

[0061] Example 12 The difference between Example 12 and Example 1 is that the mass ratio of ammonium sulfate to NaHSO3 is fixed at 2.2:1; the total mass of ammonium sulfate and NaHSO3 is 1.0% of the mass of acrylic acid, and everything else is the same as in Example 1.

[0062] Example 13 The difference between Example 13 and Example 1 is that the mass ratio of ammonium sulfate to NaHSO3 is fixed at 2.2:1; and the total mass of ammonium sulfate and NaHSO3 is 1.2% of the mass of acrylic acid.

[0063] Example 14 The difference between Example 14 and Example 1 is that the mass ratio of ammonium sulfate to NaHSO3 is fixed at 2.2:1; the total mass of ammonium sulfate and NaHSO3 is 1.4% of the mass of acrylic acid, and everything else is the same as in Example 1.

[0064] Example 15 The difference between Example 15 and Example 1 is that the reaction temperature of 70°C is replaced with 65°C, while the rest is the same as in Example 1.

[0065] Example 16 The difference between Example 16 and Example 1 is that the reaction temperature of 70°C is replaced with 75°C, while the rest is the same as in Example 1.

[0066] Example 17 The difference between Example 17 and Example 1 is that the reaction temperature of 70°C is replaced with 80°C; otherwise, they are the same as in Example 1. Example 18 The difference between Example 18 and Example 1 is that the reaction temperature of 70°C is replaced with 85°C, while the rest is the same as in Example 1.

[0067] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that cucumber biomass powder CBP was not prepared, nor was cucumber biomass powder CBP used to prepare P(AA-co-AM) / CBP SAP products.

[0068] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the P(AA-co-AM) SAP and cucumber biomass powder CBP were mixed without cross-linking, but only mechanically.

[0069] P(AA-co-AM) / CBP SAP was prepared in all of Examples 1 to 18. The effectiveness of the P(AA-co-AM) / CBP SAP prepared in Example 1 was then verified against that of the gels prepared in Comparative Examples 1 and 2.

[0070] Experimental verification (0) Structural confirmation Figure 4 FTIR spectra (black) of CBP, P(AA-co-AM) SAP, P(AA-co-AM) / CBP SAP, and mechanical mixtures of P(AA-co-AM) SAP and CBP. CBP exhibits typical multi-component characteristics of natural biomass. At 3378 cm⁻¹ -1 A relatively broad OH stretching vibration absorption band appears at 2928 cm⁻¹, originating from the abundant hydrogen bonding in the polysaccharide and hydrophilic components. -1 and 1056cm -1 Characteristic absorptions of CH and COC / CO in the polysaccharide backbone can be observed nearby. Furthermore, since CBP is an unpurified, whole-component cucumber biomass powder, its FTIR spectrum is at 1628 cm⁻¹. -1 and 1403cm -1 It also exhibits characteristic absorptions of the protein components in the amide I band (C=O stretching vibration) and amide II band (NH bending vibration coupled with CN stretching vibration), reflecting its complex multi-component characteristics.

[0071] FTIR spectrum of P(AA-co-AM) SAP (blue) at 3435 cm⁻¹ -1 1676cm -1 1558cm -1 and 1403cm -1 The -OH / -NH stretching vibration, C=O stretching vibration, and -COO are exhibited at these positions. - The characteristic absorption of asymmetric / symmetric stretching vibrations indicates that AA and AM have successfully formed a copolymer network.

[0072] Compared to the pure polymer, the FTIR spectrum of P(AA-co-AM) / CBP SAP (red) is highly consistent with that of unmodified P(AA-co-AM)SAP overall, but exhibits subtle but repeatable shifts: the –OH / –NH stretching vibration shifts from 3435 cm⁻¹. -1 Blue shifted to 3442cm -1 The C=O / amide I band is 1676 cm⁻¹ -1 Moved to 1677cm -1 -COO - The asymmetric stretching vibration shifted from 1558 cm⁻¹ to 1567 cm.-1 -COO - Symmetrical stretching vibration from 1403 cm -1 Moved to 1406cm -1 Furthermore, at 1055cm -1 The absorption shoulder peak at this point is attributed to the COC / CO stretching vibration of the polysaccharide component in CBP, indicating that CBP has been successfully introduced into the composite system. The aforementioned shifts were not observed in the mechanical mixture, suggesting that the spectral changes observed in the composite SAP are not due to a simple superposition of the two component spectra, but rather to changes in the local chemical environment between CBP and the P(AA-co-AM) network through intermolecular interactions such as interfacial hydrogen bonds.

[0073] In contrast, the FTIR spectrum (orange) of the mechanical mixture sample more closely resembles a simple superposition of the characteristic peaks of the two components. Its OH stretching vibration region exhibits a peak at 3333 cm⁻¹. -1 The wide envelope centered on the CBP (3378cm) -1 The difference is more pronounced, indicating that the hydrogen-bonded environment in the physical mixture is mainly dominated by the CBP component; while in the composite SAP, this envelope shifts to 3435 cm⁻¹. -1 The results are closer to pure SAP, indicating that CBP has been integrated into the polymer network rather than simply coexisting as an independent phase. In the fingerprint region, the mechanical mixture is at 1660 cm⁻¹. -1 1552cm -1 and 1400cm -1 Peak at 1046cm -1 The characteristic absorption of COC / CO in CBP is clearly preserved at 776 cm⁻¹. -1 The characteristic absorption of SAP was retained, further confirming that the two components in the mechanical mixture exist independently and do not affect each other. These results indicate that the interaction between CBP and the P(AA-co-AM) network is not a simple physical doping, but rather an effective interfacial integration achieved through intermolecular interactions such as interfacial hydrogen bonds.

[0074] Figure 5The images show scanning electron microscope (SEM) images of freeze-dried P(AA-co-AM) SAP and P(AA-co-AM) / CBP SAP, where (a) is a 50x magnified SEM image of pure P(AA-co-AM) SAP; (b) is a 200x magnified SEM image of pure P(AA-co-AM) SAP; (c) is a 1000x magnified SEM image of pure P(AA-co-AM) SAP; (d) is a 50x magnified SEM image of P(AA-co-AM) / CBP SAP; (e) is a 200x magnified SEM image of P(AA-co-AM) / CBP SAP; and (f) is a 1000x magnified SEM image of P(AA-co-AM) / CBP SAP. Figure 5 As can be seen, we performed SEM characterization on the internal morphology of P(AA-co-AM) SAP and P(AA-co-AM) / CBP SAP under an accelerating voltage of 5.0 kV. Among them... Figure 5 (a) ~ Figure 5 (c) in the image is the SEM image of P(AA-co-AM) SAP. Figure 5 (d) in Figure 5 In the image, (f) is the SEM image of P(AA-co-AM) / CBP SAP. (From...) Figure 5 (a) ~ Figure 5 As shown in (c), the internal structure of P(AA-co-AM)SAP is relatively dense overall. Although some porosity exists, the number of pores is relatively small, and some pore walls are relatively smooth. This indicates that the mass transfer channels inside the pure polymer hydrogel are limited, which is not conducive to the rapid penetration and diffusion of liquid during liquid absorption. In contrast, Figure [Figure number missing]... Figure 5 (d) in Figure 5 As shown in (f), P(AA-co-AM) / CBPSAP exhibits a more pronounced loose porous structure with abundant pores and numerous interconnected channels. Simultaneously, the relatively rough pore wall surface of the composite sample helps increase the contact area between the liquid and the hydrophilic groups within the material. This indicates that the introduction of CBP transforms the hydrogel's internal network from a denser structure to a more open three-dimensional porous structure, thus facilitating liquid permeation, diffusion, and storage. This aligns with the higher liquid uptake ratio and faster liquid uptake rate exhibited by the composite hydrogel.

[0075] Figure 6 The liquid absorption performance curves for P(AA-co-AM) / CBP SAP are shown below; where (a) represents the change in total initiator content; (b) represents the change in crosslinking agent content; (c) represents the change in CBP content; (d) represents the change in AA neutralization degree; and (e) represents the change in reaction temperature. Figure 6As shown in (a), when the total initiator content increases from 0.6 wt% to 1.4 wt%, the liquid absorption ratio of SAP exhibits a pattern of first increasing and then decreasing, reaching a peak at 0.8 wt%. This phenomenon can be attributed to the dual influence of initiator dosage on polymerization kinetics and network structure formation. When the initiator content is below 0.8 wt%, the number of free radical active centers in the system is insufficient, resulting in a low monomer conversion rate, incomplete polymerization reaction, and easy formation of incomplete networks with a large amount of soluble components or sparse crosslinking points. With a moderate increase in initiator dosage, the free radical generation rate increases, promoting polymer chain growth and network perfection, thereby constructing a gel with an effective three-dimensional spatial structure and improving swelling capacity. Conversely, when the initiator content exceeds 0.8 wt%, the system generates excessive free radicals in the early stage of the reaction, significantly increasing the probability of chain termination. According to kinetic principles, this leads to a shortening of the average kinetic chain length and a decrease in polymer molecular weight. Networks constructed by short-chain molecules often have small pore sizes, which limits the expansion ability of the gel network during water absorption, ultimately leading to a decrease in water absorption performance. Meanwhile, due to the multi-component structure of CBP, the multiphase surface of CBP provides more potential interfacial interaction sites. If there is an excess of free radicals, it is easier to form local cross-linking and densification at the particle and interface, thereby amplifying the swelling-limited effect under high initiator conditions.

[0076] pass Figure 6 As shown in (b), according to Flory's theory, crosslinking density is the main factor controlling the swelling capacity of SAP. Even a small change in the crosslinking agent content can lead to a significant change in the macroscopic water absorption capacity of SAP. As shown in the figure, when the MBA content increases from 0.02 wt% to 0.04 wt%, the water absorption capacity of SAP increases significantly. However, when the MBA content is greater than 0.04 wt%, the water absorption capacity of SAP decreases, and when the MBA content is 0.04 wt%, the water absorption capacity of SAP reaches its maximum. The main reason is that when the MBA content is below 0.04 wt%, the crosslinking density is low, which prevents the polymer chains from effectively forming a structurally complete three-dimensional network through chemical bonds. Additionally, some SAP transforms into water-soluble resin after water absorption, resulting in low polymer density and reduced binding force with water, thus leading to poor water absorption capacity of SAP. When the MBA content exceeds 0.04 wt%, the excessively high crosslinking density leads to a smaller average pore diameter in the network and smaller molecular chain segments between crosslinking points. This increases the elastic recoil force of SAP during water absorption and swelling, limiting the expansion of the SAP network structure and hindering the entry of water molecules, thus deteriorating its water absorption performance. It is worth noting that CBP, as a multi-component biomass powder, can provide effective crosslinking points through hydrogen bonds and ion association on the polysaccharide or protein surface. Therefore, under conditions of excessive MBA, network over-densification is more likely to occur, leading to a decrease in liquid absorption performance.

[0077] pass Figure 6 As shown in (c), the liquid absorption capacity of SAP gradually increases as the CBP content increases from 6 wt% to 10 wt%. However, when the CBP content continues to increase and exceeds 10 wt%, the liquid absorption capacity decreases, exhibiting a pattern of first increasing and then decreasing. This phenomenon can be attributed to the dual role of CBP in network construction: at lower addition levels (≤10 wt%), the hydroxyl and other functional groups in the CBP component can provide more sites for interaction in the copolymer network. Simultaneously, its hydrophilicity helps improve the gel's affinity for water and promotes the formation of a more complete and uniform three-dimensional network structure, thereby enhancing swelling capacity. When the CBP content is too high (>10 wt%), the system viscosity increases, mass transfer and free radical diffusion are restricted, making the polymerization and crosslinking processes more prone to local heterogeneity. Furthermore, excessive CBP occupies a volume fraction in the network as solid particles, reducing the effective swelling space and limiting the extension of network segments. Furthermore, an excessive number of reaction sites may cause free radicals to more readily form multi-point connections on the surface of the CBP component, leading to an increase in the local cross-linking density of the network and ultimately reducing the gel's free swelling capacity. Therefore, a formulation with 10 wt% CBP exhibits the best liquid absorption performance.

[0078] pass Figure 6 As shown in (d) of the figure, when the degree of neutralization of acrylic acid increases from 65% to 85%, the liquid absorption capacity reaches its optimum at 75%: the absorption capacity of deionized water is 2801.00 g / g, and the absorption capacity of physiological saline is 142.72 g / g. At a lower degree of neutralization (65%), the absorption capacity is only 987.08 g / g (DI) and 80.16 g / g (0.9% NaCl), mainly because the number of ionized –COO⁻ in the system is insufficient, the electrostatic repulsion and osmotic pressure driving force are weak, and the unneutralized AA is more prone to self-polymerization, resulting in a network structure and chain segment distribution that is not conducive to sufficient swelling. As the neutralization degree increases to 75%, the increased number of –COO⁻ significantly enhances segmental repulsion and Donnan osmotic pressure, making the network more prone to expansion and accommodating water molecules. However, when the neutralization degree continues to rise to 85%, the charge shielding and increased ionic strength caused by excess Na⁺ weaken the electrostatic repulsion between –COO⁻, leading to a decrease in the driving force for network expansion and a drop in absorption to 1184.24 g / g (DI) and 88.01 g / g (0.9% NaCl). Simultaneously, due to the introduction of CBP, the potential inorganic ions in its ash further increase the local ionic strength, making the optimal neutralization degree more likely to be 75%.

[0079] pass Figure 6As shown in (e), the effect of reaction temperature on the equilibrium swelling ratio of P(AA-co-AM) / CBP SAP is illustrated in Figure 1. Experimental results indicate that the liquid absorption performance of SAP reaches its peak at a reaction temperature of 70℃. When the temperature is below or above 70℃, the liquid absorption capacity decreases. At lower temperatures, the decomposition rate of the redox initiation system composed of APS and SBS is slow, resulting in a lower concentration of free radicals. This leads to a prolonged induction period and insufficient monomer conversion, making it difficult to form a complete three-dimensional network structure, thus limiting the liquid absorption performance of SAP. As the temperature gradually increases to 70℃, the decomposition efficiency of the initiator improves, and the concentration of free radicals in the system reaches the optimal equilibrium point. This promotes the advantage of chain growth over chain termination, which is beneficial for generating high molecular weight polymer chains and forming a uniform cross-linked network. However, when the reaction temperature further increases above 70℃, the initiator decomposes too quickly, causing a sudden increase in the concentration of free radicals and a sharp increase in the number of active centers. This causes the chain termination rate to significantly exceed the chain growth rate, resulting in shorter polymer chains and a lower molecular weight. Meanwhile, an excessively high reaction rate may lead to excessively high crosslinking density or uneven distribution, resulting in an overly dense gel network that reduces the free space for water molecules, ultimately leading to a decrease in the absorbency performance of SAP.

[0080] Figure 12 For the XRD diagrams of P(AA-co-AM) SAP, P(AA-co-AM) / CBP SAP, and CBP, through... Figure 12It can be seen that CBP exhibits a relatively broad diffraction peak at 2θ≈21.0°, indicating that cucumber biomass powder possesses a certain degree of short-range ordered structure, generally exhibiting a structural characteristic of being dominated by an amorphous phase accompanied by weakly ordered regions. Pure P(AA-co-AM) shows a significantly broadened diffuse peak near 2θ≈23.0°, with a weak shoulder peak appearing in the approximately 35°~40° range, indicating that the polymer network itself is mainly an amorphous structure. Compared with pure P(AA-co-AM), the main diffuse peak of the P(AA-co-AM) / CBP composite hydrogel still maintains its broad peak characteristic, but the peak position shifts slightly to 2θ≈22.3°, and the peak shape further broadens, indicating that the introduction of CBP did not form a new obvious crystalline phase, but rather further disturbed the original orderly stacking between polymer chain segments. The results indicate that during the free radical graft polymerization process, strong intermolecular interactions occurred between the polysaccharides and other biomass components in CBP and the P(AA-co-AM) network, transforming the system from a locally ordered stacked structure to a more loose and disordered three-dimensional cross-linked structure. Simultaneously, the absence of sharp diffraction peaks in the composite sample also suggests that CBP is relatively uniformly dispersed within the gel network. Typically, this amorphous network-dominated structure is more conducive to increasing free volume, exposing more hydrophilic sites, and promoting water molecule diffusion, thus consistent with the high liquid uptake ratio and fast liquid uptake rate exhibited by this material. Combined with FTIR and XRD results, it is clear that CBP has been successfully incorporated into the P(AA-co-AM) hydrogel network and exhibits significant interactions with the polymer segments, indicating that CBP participates in the construction of the hydrogel network structure.

[0081] (0) Performance verification (1) Test method for the absorption ratio of superabsorbent resin in deionized water (0.9% NaCl) Natural filtration method: Weigh approximately 0.2000g of the sample to be tested and pour it into a beaker containing sufficient deionized water (0.9% NaCl). Soak for 30 minutes to fully absorb the solution. After suspending the sample in a static state for 10 minutes, filter it through a 100-mesh stainless steel mesh with a diameter of 10cm. (Soaking time, suspension time, and mesh size all conform to the national standard GB / T22875-2018). The only difference between this method and ISO17190-5:2020 and GB / T22875-2018 is that the standard document uses a 100-mesh tea bag. Figure 9 This is a diagram showing the state of a small sample prepared in Example 1 after deionization.

[0082] (2) Test method for centrifugal retention rate of superabsorbent resin (0.9% NaCl) Weigh approximately 0.2000g of tea bag sample, soak for 30 minutes, and centrifuge for 3 minutes at 250N (1460r / min). The only difference from ISO17190-5:2020 is that this tea bag uses a 100-mesh drawstring for closure, and the standard tea bag is made of non-porous, heat-sealed non-woven fabric. Figure 10 This is a diagram showing the state of a small sample prepared in Example 1 after deionization.

[0083] (3) Test method for the rate at which superabsorbent resin absorbs 0.9% NaCl Add a 25mm iron-core PTFE stir bar and 50g of 0.9% NaCl solution to a 100ml beaker. Place the beaker on a magnetic stirrer and start stirring at 1500r / min. Then pour 1g of SAP into the beaker and start a timer. Record the time t when the vortex in the solution in the beaker disappears as the sample absorption rate. (Refer to Appendix G of GB / T22875-2018, Determination of Absorption Rate, the test procedure is as follows: Weigh 1.000g of the sample using a balance and pour it into a 100ml beaker. Shake the beaker to evenly disperse the sample at the bottom. Measure 5.0mL of 23℃ standard synthetic reagent using a measuring cylinder, quickly pour it into the beaker containing the sample, and quickly shake the beaker to evenly disperse the sample. Pour in the standard synthetic reagent and start timing simultaneously. Stop timing and record the time the moment the liquid vortex in the beaker disappears.)

[0084] (4) Artificial urine aspiration ratio The test method for the absorbance ratio of artificial urine was the same as that for the absorbance ratio of superabsorbent resin and deionized water (0.9% NaCl). To verify the role of cucumber biomass powder in the P(AA-co-AM) crosslinking network, P(AA-co-AM) SAP without cucumber biomass powder was used as a control sample. The results showed that compared with P(AA-co-AM) SAP, the absorbance ratio of P(AA-co-AM) / CBP SAP increased from 721.15 g / g to 2801.00 g / g, the absorbance ratio of 0.9% NaCl increased from 74.98 g / g to 142.72 g / g, the absorbance ratio of artificial urine increased from 44.54 g / g to 64.83 g / g, and the centrifugation retention increased from 47.67 g / g to 73.17 g / g. This demonstrates that the introduction of cucumber biomass powder can improve the liquid absorption capacity, salt resistance, and liquid retention capacity of P(AA-co-AM) hydrogels, and its effect is not limited to cost reduction. Figure 11 The image shows the state of a small sample prepared in Example 1 after deionization. The centrifugation retention rate was 51.27% (73.17 g / g divided by 142.72 g / g).

[0085] Figure 13 The TGA curves are for P(AA-co-AM) SAP, P(AA-co-AM) / CBP SAP, and CBP. Figure 13 It can be seen that CBP exhibits obvious four-stage thermogravimetric behavior, while P(AA-co-AM) SAP and P(AA-co-AM) / CBP SAP both exhibit three-stage thermal decomposition characteristics.

[0086] For CBP, the mass loss was 4.19% in the first stage (30.50℃~107.80℃), mainly due to the evaporation of free and adsorbed water in the sample; the weight loss was 25.91% in the second stage (107.80℃~218.60℃), possibly related to the initial thermal decomposition of soluble sugars, pectin, hemicellulose and some small molecule components in the biomass; the mass loss was further 21.04% in the third stage (218.60℃~329.40℃), corresponding to the continuous cleavage of the relatively stable polysaccharide backbone; the weight loss was 20.44% in the fourth stage (329.40℃~898.97℃), mainly due to the further carbonization and structural rearrangement of the residual organic components, with a final residual mass of 28.40%.

[0087] In contrast, pure P(AA-co-AM) hydrogel mainly undergoes three thermal decomposition stages: the first stage (30.5℃~355.8℃) results in a weight loss of 33.56%, mainly related to the removal of adsorbed water and the thermal elimination of side groups such as carboxyl and amide groups, as well as the initial network cleavage. The DTG curve shows a sharp mass loss peak in the 325℃~335℃ range, corresponding to the large-scale random breakage of the polymer backbone; the second stage (355.8℃~681℃) results in a weight loss of 27.07%, attributed to the further breakage of the polymer backbone and the disintegration of the cross-linked network; the third stage (681.1℃~898.9℃) results in a weight loss of 27.37%, mainly corresponding to the deep cleavage and carbonization of the residual organic structure, with a final residual mass of 11.97%.

[0088] For P(AA-co-AM) / CBP SAP, its DTG curve shows a local minimum at 295.4℃, indicating that the initial decomposition event can be divided into two distinct stages. The first stage (30.4℃~295.4℃) involves a weight loss of 17.68%, mainly attributed to the removal of free and bound water, and the initial decomposition of thermally unstable components in CBP (such as soluble sugars and pectin). The second stage (295.4℃~402.5℃) involves a weight loss of 16.10%, corresponding to the thermal elimination of polymer side groups and further degradation of the more stable polysaccharide components in CBP. The third stage (402.5℃~728.9℃) involves a weight loss of 23.56%, representing the main decomposition region of the composite material, involving large-scale breakage of the polymer backbone and the disintegration of the crosslinking network. The fourth stage (728.9℃~898.9℃) involves a weight loss of 30.50%, corresponding to the deep pyrolysis and carbonization of residual char, with a final residual mass of 12.12%.

[0089] Compared to pure P(AA-co-AM) SAP, the DTG curve of the composite hydrogel did not show a sharp mass loss peak in the low-temperature region; its mass loss was more gradual and distributed over a wider temperature range. Furthermore, the onset temperature of the main decomposition stage increased from 355.8 °C to 402.5 °C, and the weight loss proportion during the main chain breakage stage decreased from 27.07% to 23.56%. These observations indicate that the introduction of CBP not only delayed the thermal decomposition process of the polymer network but also made its degradation behavior more dispersed. This phenomenon is attributed to the interfacial interaction between the polysaccharide component in CBP and the P(AA-co-AM) network, thereby enhancing the structural stability of the composite network to some extent. Overall, the introduction of CBP improved the thermal stability of SAP.

[0090] Depend on Figure 3 It can be seen that the swelling mechanism of the P(AA-co-AM) / CBP composite hydrogel is as follows: Figure 3As shown, when the dried SAP powder comes into contact with water, a hydration layer rapidly forms on the surface due to the large number of hydrophilic groups (–OH contained in CBP, –COOH / –COO⁻ from AA, and –CONH2 from AM, etc.). Water molecules, driven by capillary force and concentration gradient, permeate and diffuse into the interior through surface pores and interparticle voids. Simultaneously, the original polymer-polymer hydrogen bonds within the network are gradually replaced by polymer-water hydrogen bonds, increasing chain segment flexibility and free volume, further accelerating water absorption and swelling. The core driving force enabling this composite network to achieve ultra-high swelling ratio lies in the electrostatic repulsion effect of carboxylate ions and the Donnan osmotic pressure difference caused by counterions. Since AA is partially neutralized before polymerization, a considerable proportion of -COONa exists in the network. During water absorption, these ionic groups dissociate, increasing the density of fixed negative charges (-COO-) on the polymer backbone, thereby generating significant electrostatic repulsion within the network and driving pore expansion. Simultaneously, the concentration of migratable Na⁺ ions inside the gel is higher than in the external solution, creating an osmotic pressure difference. Driven by this high osmotic pressure, a large number of external water molecules continuously and spontaneously flow into the hydrogel network until the system reaches swelling equilibrium. Furthermore, the –CONH2 groups introduced by acrylamide (AM) in the copolymer segments further enhance the network's hydrophilicity and stabilize the swollen state through dipole-water interactions and hydrogen bonds. Due to the limited crosslinking degree introduced by MBA and the constraint effect of rigid CBP components (such as the cellulose backbone), the SAP crosslinked network does not expand indefinitely. When the swelling driving force from the influx of external water molecules reaches a dynamic equilibrium with the deformation-resistant elastic recoil force of the crosslinked network and the rigid scaffold, the system reaches its final swelling equilibrium state. In this process, the untreated CBP, as a natural polysaccharide scaffold, provides continuous water molecule migration channels with its abundant –OH groups, while its rigid framework not only inhibits excessive relaxation of the polymer chains in the high-swelling state, maintaining the integrity of the gel structure after water absorption, but also endows the material with good cyclic swelling durability. Consistent with typical polyelectrolyte hydrogels, the swelling behavior of P(AA-co-AM) / CBP SAP exhibits significant salt sensitivity. Based on the measured uptake data for deionized water, 0.9 wt% NaCl solution, and artificial urine, the material's uptake capacity showed varying degrees of decrease when the external medium changed from deionized water to 0.9 wt% NaCl solution and then to complex artificial urine. This is because the high concentration of cations (such as Na⁺) in the external solution permeates into the hydrogel network and forms an electrostatic barrier or anti-ion association with the fixed negative charges (–COO⁻) on the main chain, thus significantly weakening the electrostatic repulsion between charges. At the same time, the ion concentration difference between the internal and external solutions decreases significantly, leading to a sharp drop in the Donnan osmotic pressure driving force, which limits the further expansion of the network.Especially in artificial urine systems, in addition to the charge shielding of monovalent inorganic ions, there are also small nitrogen-containing organic molecules such as urea and creatinine. These components are very likely to form competitive hydrogen bond associations with –COOH and –CONH2 in the network, which reduces the binding effect between polymer chain segments and water molecules, resulting in a more significant decrease in the liquid absorption ratio of composite hydrogels in artificial urine.

[0091] To further verify the performance level of the self-made SAP of this invention, the same tests were also conducted on commercially available SAPs, including Wanhua 500, Wanhua 900, Shandong Nuoer NR-610S, Sumitomo 60N, Formosa Plastics GK402, Satellite CR-710, Sanya IM-33X, LG 810ND, Nippon Shokubai QX-W-1683, Yangzi BASF N7059, and Yangzi BASF N2330. The self-made comparative example 1 P(AA-co-AM) SAP and the self-made example 1 P(AA-co-AM) / CBP SAP were used as test samples and compared with the aforementioned commercially available products, as detailed below. Table 2 shows the absorbency test results of superabsorbent resin in deionized water and 0.9% physiological saline. As shown in Table 2, the P(AA-co-AM) / CBP SAP absorbance ratio and saline absorption ratio prepared by this invention are higher than those of commercially available products.

[0092] Table 3 shows the test results of superabsorbent polymer retention (0.9% physiological saline) after centrifugation. As shown in Table 3, the centrifugation retention rate of the P(AA-co-AM) / CBP SAP prepared in this invention is much higher than that of commercially available products.

[0093] Table 4 shows the test results of the 0.9% saline aspiration rate (s). As shown in Table 4, the P(AA-co-AM) / CBP SAP prepared in this invention has a faster liquid absorption rate than the commercially available products mentioned above.

[0094] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A P(AA-co-AM) superabsorbent hydrogel reinforced with cucumber biomass powder, characterized in that, Using water as a solvent, acrylic acid and acrylamide as reactive monomers, cucumber biomass powder as organic filler, initiator and crosslinking agent are added to induce polymerization and crosslinking reactions, followed by drying, pulverization and sieving.

2. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, The mass of acrylic acid is 27.5% of the mass of water, and the mass ratio of acrylic acid to acrylamide is 2:

1.

3. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, The amount of cucumber biomass powder added is 6% to 14% of the mass of acrylic acid.

4. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, The initiators are ammonium persulfate and NaHSO3, with the total mass of the initiators being 0.6% to 1.4% of the mass of acrylic acid. The mass ratio of ammonium persulfate to NaHSO3 is fixed at 2.2:

1.

5. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, The crosslinking agent is N,N'-methylenebisacrylamide, and the mass of the crosslinking agent is 0.02%~0.06% of the mass of acrylic acid.

6. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, Sodium hydroxide was also added to the reaction system to adjust the degree of neutralization of acrylic acid to 65%~85%, and the mass of NaOH was 36.1%~47.2% of the mass of acrylic acid.

7. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, The reaction temperature of the reaction system is 65℃~85℃.

8. The cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1, characterized in that, The P(AA-co-AM) superabsorbent hydrogel reinforced with cucumber biomass powder achieved an adsorption rate of 142.72 g / g for 0.9% NaCl and an adsorption rate of 2801.00 g / g for deionized water. The central vortex disappeared after 48 seconds of adsorption of 0.9% NaCl, and the centrifugal retention was as high as 73.17 g / g, with a centrifugal retention rate of 51.27%.

9. The method for preparing cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claims 1-8, characterized in that, Includes the following steps: Preparation of cucumber biomass powder; Cucumber biomass powder was mixed with deionized water, heated and stirred to disperse, and a uniform cucumber biomass dispersion system was obtained. While maintaining the temperature, acrylamide solution and acrylic acid solution with a certain degree of neutralization were stirred and added to the cucumber biomass dispersion system. Then, a crosslinking agent and an initiator were added in sequence to carry out a crosslinking copolymerization reaction. After the reaction was completed, the product was cooled and taken out, immersed in anhydrous ethanol and filtered, dried to constant weight, pulverized and sieved to obtain P(AA-co-AM) superabsorbent water resin.

10. The application of the cucumber biomass powder-reinforced P(AA-co-AM) superabsorbent hydrogel according to claim 1 in hygiene care products.